The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.3109/01485017808988351
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological and Physiological Features after Steroid Treatment of Male Rats

Abstract: The effects of medroxyprogesterone acetate (Provera), testosterone propionate (TP), ethinyl estradiol (EE), and ethynodiol diacetate (ED) treatments on sperm population in different segments of the male rat reproductive tract, reproductive organ weights, circulating androgens and fertility were studied. Ten pg TP given for five days reduced the sperm population and organ weights. A marked reduction in the number of sperm and reproductive organ weights was observed in males orally treated with estrogens. Only l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This effect is also explained by the metabolic properties of testosterone and its metabolites. Simultaneous treatment of TP and fruit extract reduced the weight as function is naturally influenced by androgen [31]. TP treatment along with administration of fruit extract reduced the weight of the accessory reproductive organs in castrated rats in comparison to TP-treated castrated rats proves the antiandrogenic nature of the extract.…”
Section: Discussionmentioning
confidence: 95%
“…This effect is also explained by the metabolic properties of testosterone and its metabolites. Simultaneous treatment of TP and fruit extract reduced the weight as function is naturally influenced by androgen [31]. TP treatment along with administration of fruit extract reduced the weight of the accessory reproductive organs in castrated rats in comparison to TP-treated castrated rats proves the antiandrogenic nature of the extract.…”
Section: Discussionmentioning
confidence: 95%
“…The decrease in the weight of seminal vesicles, both full and void of its secretory contents, show that flutamide led to depression of cell division and regeneration of the organ and also its secretory activity. The accessory sex organs have been reported to be androgen dependent and thus reflects the availability of androgens (Hunt et al -1978). The weights of the accessory sex organs in castrated rats have been widely used as a bioassay for androgenic and antiandrogenic compounds (Neumann and Steinbeck -1974).…”
Section: Discussionmentioning
confidence: 99%
“…Flutamide treatment in the adult rat exerted a strong inhibition on the epididymis, seminal vesicles, and ventral prostate as evidenced by the ANDROLOGIA 24, 113-116 (1992) decrease in weights. It has been reported that the accessory sex organs are androgen dependent and thus reflect the availability of androgens (Hunt et al, 1978). The antiandrogenic effects of flutamide on the male sex structures were explained as the consequence of inhibition of androgen uptake and/or inhibition of nuclear binding of the androgens in the target tissues (Peets et al, 1974).…”
Section: Discussionmentioning
confidence: 99%